2016
DOI: 10.1111/his.12920
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase (TERT) promoter mutation analysis of benign, malignant and reactive urothelial lesions reveals a subpopulation of inverted papilloma with immortalizing genetic change

Abstract: TERT promoter mutations were found in 15% of inverted papillomas. Our data suggest that there is a subpopulation of inverted papilloma that shares a carcinogenetic pathway with urothelial carcinoma with inverted growth and conventional urothelial carcinomas. Caution is warranted in exploring TERT promoter mutation status as a screening or adjunct diagnostic test for bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 28 publications
1
32
5
Order By: Relevance
“…With the exception of the case outlined above and contrasting prior reports in the literature , none of the other IUP or UP tumors had TERT promoter or activating FGFR3 mutations. Similarly, in contrast to urothelial carcinomas, oncogenic alterations in chromatin remodeling genes were uncommon in both IUP and UP, being identified in only one IUP and two UP cases.…”
Section: Resultscontrasting
confidence: 80%
“…With the exception of the case outlined above and contrasting prior reports in the literature , none of the other IUP or UP tumors had TERT promoter or activating FGFR3 mutations. Similarly, in contrast to urothelial carcinomas, oncogenic alterations in chromatin remodeling genes were uncommon in both IUP and UP, being identified in only one IUP and two UP cases.…”
Section: Resultscontrasting
confidence: 80%
“…Although our study found no TERT promoter mutation in any case of inverted papilloma, Cheng et al . reported TERT promoter mutations in 15% (four of 26) cases of inverted papillomas . Such a discrepancy might result from the ethnic factor or other causes; however, the potential interobserver variation may influence the accuracy of metanalysis among these studies.…”
Section: Discussionmentioning
confidence: 97%
“…Mutations in the promoter region of the TERT gene have been found not only in bladder cancer but also other types of human cancers, including malignant melanoma, thyroid carcinoma and glioma . In bladder cancer, TERT promoter mutations were found in a considerable percentage of tumour samples, regardless of the tumour stage and histological grade . Vinagre et al .…”
Section: Introductionmentioning
confidence: 99%
“…A component of conventional urothelial carcinoma is frequently present. The nested urothelial carcinoma, seen either in pure form or with a component of conventional urothelial carcinoma, has a poor outcome …”
Section: Nested Urothelial Carcinomamentioning
confidence: 99%
“…The differential diagnosis of the nested variant of urothelial carcinoma includes lesions and tumours with nested‐like morphology as prominent von Brunn nests, cystitis cystica, cystitis glandularis, inverted papilloma, nephrogenic metaplasia, carcinoid tumour, paraganglionic tissue and paraganglioma (Table ) . The large nested variant of urothelial carcinoma seems to be inter‐related to urothelial carcinoma with inverted growth, and the differential between both entities might not always be possible .…”
Section: Nested Urothelial Carcinomamentioning
confidence: 99%